2009
DOI: 10.1108/02630800910985108
|View full text |Cite
|
Sign up to set email alerts
|

Historic building information modelling (HBIM)

Abstract: Historic Building Information Modelling (HBIM) is a new approach for modelling historic buildings which develops full Building Information Models (BIMs) from remotely sensed data. HBIM consists of a novel library of reusable parametric objects, based on historic architectural data and a system for mapping theses library objects to survey data. This chapter describes the development of a library of parametric objects for HBIM that can be used to model classical architectural elements. Steps towards automating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
302
0
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(326 citation statements)
references
References 10 publications
0
302
0
24
Order By: Relevance
“…Although Building Information Modelling (BIM) is used in modern architecture for representing buildings, not only graphically but also as a hierarchy of functional parts, its concepts have been ported to the world of ancient buildings, leading to the term Heritage BIM (HBIM) (Murphy et al, 2009). This also requires an interpretation of the collected 3D data that have to be subdivided in a semantically logical way (De Luca et al, 2006).…”
Section: Data Managementmentioning
confidence: 99%
“…Although Building Information Modelling (BIM) is used in modern architecture for representing buildings, not only graphically but also as a hierarchy of functional parts, its concepts have been ported to the world of ancient buildings, leading to the term Heritage BIM (HBIM) (Murphy et al, 2009). This also requires an interpretation of the collected 3D data that have to be subdivided in a semantically logical way (De Luca et al, 2006).…”
Section: Data Managementmentioning
confidence: 99%
“…Therefore, some international researches were referenced for further studying. Murphy et al (2009) suggested HBIM to be a new system for modelling the built heritage building. This research focuses on the modelling process of buildings such as the acquisition of point clouds, meshing and integrating additional properties.…”
Section: Ontologymentioning
confidence: 99%
“…In this project, the BIM software Autodesk Revit 2016 and A360 are adopted. Murphy (2009), marked in red by the authors: the red line with an arrow is a shortcut route, the nodes in dashed rectangles are not necessary, and the final node is supposed to be extended.…”
Section: Introductionmentioning
confidence: 99%
“…Murphy (2009) put forward the concept of HBIM and found a way out for point cloud which is difficult to reuse. However, it can be argued that the workflows by Murphy is not applicable.…”
Section: Introductionmentioning
confidence: 99%